Soil fertility changes under long-term integrated nutrient management practices on acid soils of Meghalay - T, RAMESH; HAZARIKA, S; CHOUDHURY, B U; KUMAR, MANOJ; VERMA, B C; RAJASEKAR, K; NGACHAN, S V (Indian Journal of Hill Farming, 2014)
The long term residual effect of integrated use of organic and inorganic nutrient sources on soil fertility was studied at Division of Soil Science, ICAR Research Complex for NEH Region, Umiam, Meghalaya. The integrated nutrient management experiment was conducted during 2000-2005. At the end of experiment, soils from different treatments were collected and used for this study. Application of lime and FYM along with 75% recommended NPK increased the soil pH (5.02) and decreased the exchangeable Al (0.69 meq 100g-1) whereas, control plot receiving 100% recommended NPK showed the lowest pH (4.19) and highest exchangeable Al (2.39 meq 100g-1). Combined application of FYM and biofertilizers along with 75% recommended NPK increased the organic carbon content (2.28 g 100g-1) whereas organic carbon content was decreased (1.78 g 100g-1) in the treatment receiving lime and biofertilizers along with 75% recommended NPK. Application of lime and FYM along with 100% recommended NPK increased P content (59.95 kg P2O5 ha-1) whereas, it decreased P content (18.27 kg P2O5 ha-1) with zero NPK. Similarly, K content was increased (293.9 kg K2O ha-1) in the treatment receiving FYM and biofertilizer along with 75% recommended NPK while it decreased (186.4 kg K2O ha-1) in control receiving zero NPK. Exchangeable base content was low (1.41 meq 100g-1) under control with 100% recommended NPK however, highest value (3.78 meq 100g-1) was observed with the treatment receiving lime and FYM along with zero NPK.